Гидрогеохимические особенности состава азотных терм Байкальской рифтовой зоны; Геология и геофизика; Т. 54, № 5 - Плюснин А. М. Алексей Максимович; Замана Л. В. Леонид Васильевич; Шварцев С. Л. Степан Львович; Токаренко О. Г. Ольга Григорьевна; Чернявский М. К. Максим Константинович (Петрология, геохимия и минералогия, 2013)
Заглавие с экрана